Speaking with authority (Assemble You, 2022)
Welcome to Audio Learning from Assemble You. In this lesson, we look at why being able to speak with authority is so integral for leaders and how you can go about achieving this when addressing any audience - large or small. Google ""greatest speakers"", and you'll see faces like Winston Churchill and Martin Luther King Jr. Yes, they were born with brilliance, but they could also convey their aims and ideas to those around them with authority and in a way that inspired people to follow them.. As a leader, you must be able to convey your messages with authority and confidence, whether addressing your team or speaking to a packed auditorium. Unsure of how you can speak with authority without sounding like an angry teacher? Don't fret; we have some tips for you. Learning Objectives Distinguish between speaking aggressively and speaking with authority Identify strategies for effective and authoritative speaking.